Interdisciplinary consciousness studies need philosophy of science - Kirkeby-Hinrup, Asger (Filosofiska notiser, 2024)
Significant progress has been made over the last couple of decades with respect to empirical investigations of consciousness. The field of interdisciplinary consciousness studies is sprawling and growing at a rapid pace. There is, however, still much to figure out, and the philosophy of science has an important role to play in untangling the complex relationships between theory and empirical data. I start by providing a rough overview of the historical developments over the last couple of decades with an eye to how the research focus has shifted in that time. Next, I describe the current state of the field and highlight some of the core problems in interdisciplinary consciousness studies that would benefit from the involvement of philosophers of science. Finally, I summarize three contemporary endeavors in the attempt to assess and compare theories of consciousness. The goal is to convey that interdisciplinary consciousness studies is a field ripe for the application of philosophy of science, and hopefully inspire philosophers of science to come help us out.
Keywords: consciousness; Neuroscience; Cognitive Science; Empirical Evidence; Falsification; Inference to the best explanation